2013
DOI: 10.1017/s1461145713000862
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine depot formulation in rat: a step forward in modelling antipsychotic-induced metabolic adverse effects

Abstract: Rats are used as animal models in the study of antipsychotic-induced metabolic adverse effects, with oral drug administration yielding hyperphagia, weight gain and, in some cases, lipogenic effects. However, the rapid half-life of these drugs in rats, in combination with development of drug tolerance after a few weeks of treatment, has limited the validity of the model. In order to prevent fluctuating drug serum concentrations seen with daily repeated administrations, we injected female rats with a single intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 56 publications
6
43
2
Order By: Relevance
“…Consistent with the body weight changes in this study, the olanzapine-only group had more white fat mass and higher liver weight than the control and betahistine-only groups, which also corresponded with previous reports [31], [46], [51], [64], [65]. On the other hand, compared to the olanzapine-only treatment, chronic O+B co-treatment decreased inguinal fat mass and liver weight in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the body weight changes in this study, the olanzapine-only group had more white fat mass and higher liver weight than the control and betahistine-only groups, which also corresponded with previous reports [31], [46], [51], [64], [65]. On the other hand, compared to the olanzapine-only treatment, chronic O+B co-treatment decreased inguinal fat mass and liver weight in this study.…”
Section: Discussionsupporting
confidence: 92%
“…It has been found that olanzapine and clozapine activated hypothalamic AMPK by blocking H 1 Rs to increase food intake and body weight gain [63,96,97]. In hypothalamic tissue slices, the level of pAMPK can be enhanced markedly by olanzapine, which indicates that the weight gain/obesity side-effects associated with olanzapine is mediated by activation of hypothalamic AMPK linked to blockade of the histaminergic H 1 R [63].…”
Section: The Role Of Hypothalamic H 1 R-ampk Signalling In Sga-inducementioning
confidence: 99%
“…We previously demonstrated that, in the female rat, treatment with olanzapine elevated transcription of several genes involved in lipogenesis, all target genes of the key transcription factors sterol regulatory element binding proteins 1 and 2 (SREBP1 and SREBP2), independent of nutritional status (Skrede et al, 2012(Skrede et al, , 2014.…”
Section: Genementioning
confidence: 99%
“…The use of rodents facilitates screening of dysmetabolic effects in organisms not previously exposed to antipsychotic agents, but have been hampered by the short half-life of antipsychotics in rodents (Aravagiri et al, 1999). We recently circumvented this challenge by means of intramuscular injections of a long-acting olanzapine formulation, and demonstrated that such exposure gave clinically relevant plasma levels of olanzapine, associated with potent dysmetabolic effects in the female rat (Skrede et al, 2014).…”
Section: Introductionmentioning
confidence: 99%